A rebirth of radiation therapy with kV X-rays? - Kalef-Ezra, J. (HNPS Advances in Nuclear Physics, 2019)
Novel clinical approaches using kV X-ray beams are currently under study, such as selective dose enhancement in malignant tissues due to the enhanced presence of atoms with high atomic number, Z, in tumors relative to normal tissues or the use of heavily spatially fractionated kV X-ray irradiation. Local dose enhancement by high Z atoms: A substantial dose gradient between normal and malignant tissues can be achieved by biologic targeting the cells to be “destroyed” with high Z atoms and its irradiation with photons in the energy region of tens of keV, such as synchrotron produced X-rays of energy above the K-edge. The selective accumulation of high Z atoms can be achieved by various techniques, such as by intravenous administration of a) contrast enhancement agents, b) some chemotherapeutic drugs c) nanoparticles and d) DNA precursors loaded with Z-atoms. Taking into account the limited availability and the high cost of GeV synchrotrons, brachytherapy sources could be used. Microbeam radiation therapy: Studies carried out in experimental models using spatially micro- fractionated beams have shown drastically elevated tissue radiation tolerance, with higher tissue sparing in healthy tissues than in malignant ones. This phenomenon is attributed by some investigators to the proliferation and migration of cells from the “low” dosed regions (~10 Gy) to the adjacent “heavily” dosed regions (many hundreds of grays). Multi-slit collimators allow for the production of X-ray microbeam arrays at 3rd generation synchrotron units. Monte Carlo simulations were tested versus direct dose measurements. Promising preclinical studies carried out so far, trigger studies on the development of alternative less expensive technologies.